HLA‐A, ‐B, ‐DR allele group frequencies in 7007 kidney transplant list patients in 27 UK centres. (7th September 2012) - Burt, C.; Cryer, C.; Fuggle, S.; Little, A.‐M.; Dyer, P.
Summary This observational study aims to determine the HLA specificity frequencies of patients on the UK renal transplant list, which can be used as a resource for those laboratories that support the UK renal transplant programme. Whilst the HLA specificity frequencies may differ from that of the general population, it is the individuals on the transplant list who are in need of a new kidney, which has to be provided from the general population. Any differences in protein allele frequencies between this patient population and the general population are likely to be minimal because of the very large number of patients included. The HLA‐A, ‐B and ‐DR allele group frequencies from 7007 patients on the UK kidney transplant list (August, 2009) were analysed. HLA types had been submitted to NHSBT to register patients on the UK deceased donor kidney waiting list. The data were submitted from 27 different registering centres throughout the UK. Within this data set, 25 different HLA‐A, 50 HLA‐B and 18 HLA‐DR allele groups were present. The most common allele groups at each locus were ‐A2 (phenotype frequency 42.6%), ‐B44 (phenotype frequency 23.3%) and –DR4 (phenotype frequency 29.8%). The least common allele groups at each locus were ‐A19, ‐ A43, ‐B16, ‐B21, ‐B22, ‐B83 and ‐DR5. Reports of HLA frequency (protein allotype) data from populations as large as this are not readily available adding value to this observational study.